A Catalyst‐Free Minisci‐Type Reaction: the C–H Alkylation of Quinoxalinones with Sodium Alkylsulfinates and Phenyliodine(III) Dicarboxylates. Issue 41 (22nd October 2019) - Wang, Liping; Zhao, Jiquan; Sun, Yuting; Zhang, Hong‐Yu; Zhang, Yuecheng
Abstract : A direct C–H alkylation of quinoxalinones at the C‐3 position with sodium alkylsulfinates and phenyliodine(III) dicarboxylates has been developed under catalyst‐free conditions. A series of 3‐alkylquinoxalinones were afforded in moderate to excellent yields in this protocol, which offers a practical and efficient access to biologically interesting 3‐alkylquinoxalin‐2(1 H )‐one derivatives. Abstract : A direct C–H alkylation of quinoxalinones at the C‐3 position with sodium alkylsulfinates and phenyliodine(III) dicarboxylates has been developed under catalyst‐free conditions. A series of 3‐alkylquinoxalinones were afforded in moderate to excellent yields in this protocol, which offers a practical and efficient access to biologically interesting 3‐alkylquinoxalin‐2(1 H )‐one derivatives.